Legal framework pecularities for arresting of seagoing ships in Lithuania - Дробітко, Олег Георгійович; Дробитько, Олег Георгиевич; Drobitko, Oleg (Одеса : Видавничий дім «Гельветика», 2018)
The present article aims at presenting the legal framework peculiarities for arresting of seagoing ships in Lithuania. Analysis on the ratified Maritime Law Convention and national legislation within the said field. Comparison of the definitions of maritime claim, privileged claims, maritime liens and their peculiarities in Lithuania. Analysis on the main legal relations between maritime claims of the participants taking part in civil and other procedures. Analysis on which courts in Lithuania may grant an arrest of seagoing ships as a security for claims. Analysis on the legal framework for release of arrested seagoing ships. The present article also presents a brief analysis on the measures for releasing arrested ships, i.e., payment of the security of the required amount or provision of other guarantee and provides a brief synopsis on the financial products offered by the members of the International Group of P&I Clubs.

Статтю присвячено короткому аналізові правового регулювання арешту морських суден у Литві. Аналізуються ратифіковані конвенції приватного морського права, національне законодавство в цій сфері. Порівнюються і аналізуються дефініції морської претензії, привілейованої претензії, морський застави та їх особливості в Литві. У статті аналізуються основні випадки правовідносин між учасниками цивільного та інших процесів на основі морських вимог. Аналізується які суди Литви можуть застосовувати арешт морського судна як засіб забезпечення морської вимоги. Проаналізовано правове регулювання звільнення морського судна від арешту. Коротко аналізуються шляхи звільненого судна, такі як внесення необхідної суми застави або надання іншої гарантії, висвітлюються фінансові продукти членів Міжнародної групи клубів P&I.

Статья посвящена краткому анализу правового регулирования ареста морских судов в Литве. Анализируются ратифицированные конвенции частного морского права, национальное законодательство в этой сфере. Сравниваются и анализируются дефиниции морской претензии, привилегированной претензии, морского залога и их особенности в Литве. В статье рассматриваются основные случаи правоотношений между участниками гражданского и других процессов на основании морских требований. Анализируется какие суды Литвы могут применять арест морского судна как средство обеспечения морского требования. Проанализировано правовое регулирование освобождения морского судна от ареста. Коротко анализируются способы освобожденного судна, такие как внесение необходимой суммы залога или предоставления другой гарантии, освещаются финансовые продукты членов Международной группы клубов P&I.
Drobitko O. Legal framework pecularities for arresting of seagoing ships in Lithuania / O. Drobitko // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), І. В. Сафін (заст. голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2018. - № 2. – C. 7-20.
Keywords: ship arrest; maritime claim; privileged claims; maritime liens; security; guarantee; P&I Club; арешт судна; морська претензія; привілейована вимога; морська застава; заставний депозит; гарантія; P&I Club; арест судна; морская претензия; привилегированное требование; морской залог; залоговый депозит; гарантия; P&I Club